2015
DOI: 10.1242/jcs.172288
|View full text |Cite
|
Sign up to set email alerts
|

MyoD transcription factor induces myogenesis by inhibiting Twist-1 through miR-206

Abstract: Twist-1 is mostly expressed during development and has been previously shown to control myogenesis. Because its regulation in muscle has not been fully exploited, the aim of this project was to identify micro (mi)RNAs in muscle that regulate Twist-1. miR-206, one of the most important muscle-specific miRNAs (myomiRs), was identified as a possible regulator of Twist-1 mRNA. Luciferase assays and transfections in human foetal myoblasts showed that Twist-1 is a direct target of miR-206 and that through this pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 61 publications
0
29
0
1
Order By: Relevance
“…Compared to mocked control cells, si-DNMT3B samples showed of a marked expression of MYOD1, followed by Myogenin and myomiR (miR-133a and miR-206) up-regulation. MYOD1 is a master regulator of myogenesis, since it normally triggers the down-stream molecular events that switch myoblasts from a growing phase to a differentiated state, by directly promoting the expression of miR-206 and many other genes involved in myogenesis [45, 46]. RD proliferating cells show low levels of MYOD1, and increased abundance of this transcription factor has been demonstrated to fully execute the terminal myogenic program [47], this confirming that a controlled amount of MRFs is a fundamental condition for proper skeletal muscle differentiation in ERMS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to mocked control cells, si-DNMT3B samples showed of a marked expression of MYOD1, followed by Myogenin and myomiR (miR-133a and miR-206) up-regulation. MYOD1 is a master regulator of myogenesis, since it normally triggers the down-stream molecular events that switch myoblasts from a growing phase to a differentiated state, by directly promoting the expression of miR-206 and many other genes involved in myogenesis [45, 46]. RD proliferating cells show low levels of MYOD1, and increased abundance of this transcription factor has been demonstrated to fully execute the terminal myogenic program [47], this confirming that a controlled amount of MRFs is a fundamental condition for proper skeletal muscle differentiation in ERMS cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are crucial players in many pathophysiological processes owing to their promising potential of being novel diagnostic and predictive markers for therapies. Previous studies demonstrated that several miRs can stimulates the expression of Twist [ 34 - 36 ]. In this study, Twist is identified as a new direct target of miR-497.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other pathways involving miRNAs and the regulation of myogenesis, hypertrophy, or atrophy have been described both in vitro and in vivo . Koutalianos et al ( 53 ) showed that overexpression of MyoD, a myogenic transcription factor, induces the expression of miR-206. In addition, the increase of miR-206 downregulates Twist-1, decreasing the activity of Twist-1, and allowing increased differentiation of muscle cells.…”
Section: Myomirs and Cancer Cachexiamentioning
confidence: 99%
“…The authors reported that muscle cells from patients with myotonic dystrophy type 1 exhibited inhibition of MyoD protein expression and an increase of Twist-1 expression, following a reduction in miR-206 levels. The co-transfection of MyoD and miR-206 regulated the protein content of Twist-1, allowing the differentiation of muscle cells to occur ( 53 ).…”
Section: Myomirs and Cancer Cachexiamentioning
confidence: 99%
See 1 more Smart Citation